Pelatihan Pengisian Beban Kerja Dosen (BKD) Berbasis Sistem Informasi Sumber Daya Terintegrasi (SISTER) - Iryani Iryani; Harry Yulianto (To Maega : Jurnal Pengabdian Masyarakat, 2023)
Lecturer Workload (BKD) is a detailed report on Tri Dharma Higher Education activities carried out by lecturers which includes education and teaching activities, research, community service, and supporting activities which are reported every semester. The purpose of the training activities is to increase lecturers' knowledge, understanding and skills in filling out BKD through SISTER, increase lecturers' understanding of BKD provisions in accordance with applicable operational guidelines, and increase lecturers' awareness of the obligation to complete portfolio evidence for filling in BKD independently through SISTER. The methods used to achieve the training objectives are lecture, practice and discussion methods. The results show that there is an increase in lecturers' understanding of training materials and awareness for filling out the BKD portfolio through SISTER. Recommendations for further activities in order to improve the quality and career development of lecturers, namely training in the publication of scientific articles, training and writing community service activities in community service journals.